Biodiversity of marine red algae (Rhodophyta) in Tabasco, México - Quiroz-González, Nataly; León-Álvarez, Daniel; Rivas-Acuña, Ma. Guadalupe (Instituto de Ecología, A.C., 2018)
Background and Aims: The knowledge of the phycoflora in the state of Tabasco is scarce. There are 39 records of Rhodophyta, 7 of Ochrophyta and 22 of Chlorophyta. In addition, at national level it is the coastal state with the lowest number of publications on the subject. The present work was developed to contribute to the knowledge of the algal flora of the state, particularly that of Rhodophyta.Methods: Material from the herbaria of the Faculty of Sciences (FCME) of the Universidad Nacional Autónoma de Mexico (UNAM) and the Universidad Juárez Autónoma de Tabasco (UJAT) was studied. Two sampling periods were carried out in dry and rainy season of 2012, in seven localities of the coast of Tabasco. The collected material was preserved in formaldehyde at 4%. Sections were performed with stereoscopic and optical microscopes. Identification was carried out with specialized literature.Key results: Twelve new records of marine red algae species are reported from the coast of Tabasco, belonging to 11 genera, 9 families and 8 orders. In total, for Tabasco there are 52 species, 32 genera, 17 families and 10 orders. The orders with the highest species richness are Ceramiales and Gracilariales with 24 and 9 species, respectively. The families with the highest number of species are Rhodomelaceae and Gracilariaceae with 14 and 8 each one. The most diverse genus was Gracilaria, with eight species.Conclusions: The number of red seaweeds recorded in Tabasco raises from 39 to 52 reports, representing 20% of the Rhodophyta species recorded for the Gulf of Mexico.